An overview of assessment methods and analysis for climate change risk in China. (June 2020) - Feng, Aiqing; Chao, Qingchen
Abstract: Climate warming and subsequent climate extremes have a wide impact on ecosystems and economic society. Scientifically quantitative assessment on climate change risks is an urgent issue attracted the attention of academics and decision-makers. In this paper, the theory of climate change risks was sorted out based on the three component elements of hazard, vulnerability, and exposure. Moreover, the idiomatic assessment methods and their applicability were systematically summarized. Comprehensive analysis found that the impacts of climate change generally showed a negative trend that was more harm than benefit, and further warming would aggravate the risk over China which was manifested to be more prominent in some sensitive sectors and key regions to climate change. Accessible management of the climate change risk should be engaged in effectively improving the methods of comprehensive identification, strengthening the mechanism and quantitative assessment, recognizing the temporal and spatial variation of components related to climate change risk, and reducing the uncertainty of climate change projection. Highlights: Theoretical framework of climate change risk was formed based on hazard, vulnerability, and exposure. Assessment methods of climate change risk and their applicability were systematically summarized. Climate change risk levels were analyzed in sensitive sectors and key regions over China. In China, impacts of climate change were more harm than benefit while more warming was very likely to aggravate the risk.